Brane-world cosmology and varying G - Amarilla, Leonardo (2010)
We consider a brane-world cosmological model coupled to a bulk scalar field. Since the brane tension turns out to be proportional to Newton’s coupling G, in such a model a time variation of G naturally occurs. By resorting to available bounds on the variation of G, the parameters of the model are constrained. The constraints coming from nucleosynthesis and CMB result to be the severest ones.